Is it possible to use autologous adipose graft for wound repair in patients with coagulation disorders?. (20th September 2015) - Caviglia, H.; Landro, M. E.; Gallo, E.; Douglas Price, A. L.; Galatro, G.; Neme, D.
Abstract : Introduction: Wound healing is an intricate process whereby the skin repairs itself after injury according to a specific sequence: haemostasis, inflammation, proliferation and remodelling. Cell therapy has the potential to improve wound healing conditions and can be applied in both acute and chronic wounds. Normal healing requires adequate haemostatic function. Patients with coagulation disorders whose haemostatic function is altered may not heal naturally. Aim: The aim of this study was to show a simple, safe and inexpensive minimally invasive technique for wound repair in patients with coagulation disorders which involves the use of concentrated autologous adipose cells. Patients and method: Six patients were enrolled in this study at the Foundation of Haemophilia, in Buenos Aires, Argentina. Five patients had severe haemophilia type A and one had severe von Willebrand diseases. The average age was 37.5 years old. One patient had a retractile scar (RS) and five patients had cutaneous fistulas (CF). Suction was used to obtain autologous adipose graft from subcutaneous abdominal tissue. The graft was centrifuged and, the adipose cell concentrate was transferred to a syringe and injected in the edge of the lesion. Results: One adipose suction in each patient was performed. There were no intraoperative or postoperative complications in any of the six patients. Conclusions: The application of autologous adipose graft is a simple and safe treatment for complicated wound repair in patients with coagulation disorders.